The Role of Valuers in Leveraging Big Data in Real Estate Industry in Malaysia - Azrul Thani, ‘Atiqah Najwa; Esha, Zulkifli (Research in Management of Technology and Business, 2024)
Big data, originating in the 1990s, is a vast and complex datasets that surpasses the capacity of traditional data management tools. The International Business Corporation Machines claimed that daily data creation reaches 2.5 quintillion bytes, indicating the complexity nature of big data. Apart from its sheer volume, the complexity also arises from its attributes such as velocity, and veracity as reflected in the 7Vs framework. Transitioning to the real estate sector, big data has a major influence on Malaysia’s real estate market. Big data adoption enhances the transparency and reliability of the market, benefiting both buyers and sellers. Given its position as a significant driver of economic growth, the real estate market is influenced by diverse factors namely economic conditions, market trends and others. As the market is dynamic and constantly changing, it is imperative that big data is employed in the industry. The central focus of this research is on the vital role of valuers in leveraging big data in the real estate industry in Malaysia to gain accurate and precise valuation. This research addresses three key questions, exploring factors encouraging big data adoption among valuers, the impacts of the adoption and the challenges faced in daily operations. The study uses a quantitative approach, relying on primary data from surveys, to assess real-world scenarios and experiences of valuation practice and big data utilization. In conclusion, this research provides a detailed exploration on the relevance of big data in the real estate sector and serves as a foundation for future studies to harness the full potential of big data in real estate practice.